BIODIVERSITY, DISTRIBUTION, AND ABUNDANCE OF THE TROPICAL ANGUILLID EELS IN THE INDONESIAN WATERS - Sugeha, Hagi Yulia; Suharti, Sasanti Retno; Wouthuyzen, Sam; Sumadhiharga, Kurnaen (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
In order to understand biodiversity, distribution, and abundance among the tropical anguillid eels in the Indonesian waters, inshore migration mechanism of the juvenile anguillid eel (glass eel) to the estuaries of western, central, and eastern region of Indonesian waters were examined using both morphology and genetic analyses. A total of 9 species/sub species of anguillid eels (Anguilla bicolor bicolor, A. nebulosa nebulosa, A. bicolor pacifica, A. interioris, A. borneensis, A. celebesensis, A. marinorata, A. obscura and A. megastoma) were recognized to recruit at the mouth of 15 rivers through Indonesian archipelago. Species/subspecies diversity and distribution of recruiting juveniles differs in the estuaries of each region. In the western region that represented by estuary of Krueng Aceh, Batang Antokan, Air Kertaun, Cibaliung, Citanduy, Progo, and Pacitan Rivers, three species and sub species (A. bicolor bicolor, A. nebulosa nebulosa and A. bicolor pacifica) were found. In the central region that represented by estuary of Mahakam, Palu, Dumoga, Poigar, Bone, and Poso Rivers, five species and sub species (A. borneensis, A. celebesensis, A. marinorata, A. bicolor pacilica and A. interioris) were found. In the eastern region that represented by estuary of Akelamo and Pami Rivers, four species (A. marinorata, A. interioris, A. obscura and A. megastoma) were found. During the 6 months investigation from May to October 2005, abundance of the juveniles was higher in the central region compared with western and eastern regions. These results were suggested that inshore migration mechanism of tropical anguillid eels recruiting in tropical estuaries of Indonesian waters differs among regions.